2019
DOI: 10.2105/ajph.2019.305123
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Reduce Ageism Against Older Adults: A Systematic Review and Meta-Analysis

Abstract: Background. Research has found a strong link between ageism, in the form of negative stereotypes, prejudice, and discrimination toward older people, and risks to their physical and mental health. Little is known, however, about the effectiveness of strategies to reduce ageism. Objectives. To assess the relative effects of 3 intervention types designed to reduce ageism among youths and adults—education, intergenerational contact, and combined education and intergenerational contact—by conducting a systematic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
260
4
30

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 397 publications
(346 citation statements)
references
References 82 publications
12
260
4
30
Order By: Relevance
“…Experimental evidence has shown that informing individuals about stereotype threat ( Mazerolle et al, 2016 ) and promoting either experienced or imagined intergenerational contact ( Abrams et al, 2006 , 2008 ) reduced the negative effects of stereotype threat on older adults’ cognitive performance. The latter approach may be particularly promising, as intergenerational contact can also improve stereotypes and attitudes toward older people (for reviews, see Burnes et al, 2019 ; Marques et al, 2020 ). Still, intergenerational programs focusing on technology use must be carefully designed, as they may end up reinforcing stereotypical perceptions of older adults as incompetent ( Drury et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence has shown that informing individuals about stereotype threat ( Mazerolle et al, 2016 ) and promoting either experienced or imagined intergenerational contact ( Abrams et al, 2006 , 2008 ) reduced the negative effects of stereotype threat on older adults’ cognitive performance. The latter approach may be particularly promising, as intergenerational contact can also improve stereotypes and attitudes toward older people (for reviews, see Burnes et al, 2019 ; Marques et al, 2020 ). Still, intergenerational programs focusing on technology use must be carefully designed, as they may end up reinforcing stereotypical perceptions of older adults as incompetent ( Drury et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our review departed from a vast pool of studies, which allowed us to minimise searching bias but delayed time from searching to dissemination. We decided to not conduct an immediate update to keep our strategy consistent with the remainder of projects developed in the context of the same initiative-the Global Campaign to Combat Ageism of the WHO [22][23][24][25]. While our work is the first systematic review effort on this topic and sets bases for future endeavours within the same scope, we acknowledge it may be important to revisit this topic in a few years for an update (may further developments in the field justify).…”
Section: Limitations and Recommendations For Future Studiesmentioning
confidence: 99%
“…Ultimately, we hope the findings from this systematic review may help to inform the development and expansion of intervention programs aimed at tackling ageism, including the Global Campaign to Combat Ageism that is being led by the World Health Organization (WHO) [22][23][24][25]. In addition, we also aimed to identify and discuss specific research gaps in the determinants of ageism literature where further studies may be beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…Third, the use of arbitrary age cut-offs and the generalized (mis)attribution of COVID-19 risk to aging has inadvertently reinforced and intensified negative age stereotypes, prejudice, and discrimination that will need to be addressed (Ayalon et al, 2020;Brooke & Jackson, 2020;Meisner, 2020). Even before the pandemic, interventions aiming to reduce ageism were essential and thus should be developed further (Burnes et al, 2019).…”
Section: Critical Views On Aging Amid Covid-19: a Call For More Geronmentioning
confidence: 99%